1979
DOI: 10.3406/bulmi.1979.7307
|View full text |Cite
|
Sign up to set email alerts
|

Contribution à l'étalonnage de la pression interne des inclusions fluides lors de leur décrépitation

Abstract: La pression à l'intérieur d'une inclusion augmente avec la température. Lorsque cette pression devient supérieure à la résistance des parois de l'inclusion, celle-ci décrépite. Des travaux antérieurs effectués sur des quartz synthétiques ou naturels, par décrépitométrie ou par microthermométrie, conduisent à des valeurs différentes de la pression de décrépitation. La taille des inclusions est un des facteurs considérés comme responsables de ces variations de la pression. De nouvelles valeurs ont ét… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 0 publications
2
33
1
Order By: Relevance
“…CH 4 loss could be inversely proportional to inclusion size. This result is not in accordance with the data of Vityk and Bodnar (1995) regarding isothermal decompression in quartz, or with experiments conducted at 1 atm which have indicated the decrepitation of large inclusions at lower effective pressure than smaller inclusions (Leroy, 1979;Bodnar and Bethke, 1984;Bodnar et al, 1989) in quartz and fluorite. For experiments conducted at 1 atm, the discrepancy can be explained by the fact that internal overpressure was generated by overheating of inclusions.…”
Section: Petrographic Implicationscontrasting
confidence: 77%
See 1 more Smart Citation
“…CH 4 loss could be inversely proportional to inclusion size. This result is not in accordance with the data of Vityk and Bodnar (1995) regarding isothermal decompression in quartz, or with experiments conducted at 1 atm which have indicated the decrepitation of large inclusions at lower effective pressure than smaller inclusions (Leroy, 1979;Bodnar and Bethke, 1984;Bodnar et al, 1989) in quartz and fluorite. For experiments conducted at 1 atm, the discrepancy can be explained by the fact that internal overpressure was generated by overheating of inclusions.…”
Section: Petrographic Implicationscontrasting
confidence: 77%
“…Larson et al (1973), and subsequently other authors (Leroy, 1979;Swanenberg, 1980;Pêcher, 1981;Lawler and Crawford, 1983;Bodnar and Bethke, 1984;Grattier and Jenatton, 1984;Guilhaumou et al, 1987;Prezbindowski and Larese, 1987;Bodnar et al, 1989;Meunier, 1989) have suggested that interpretations of thermal disequilibrium between ''hot" fluids and ''cold" rock were probably misinterpreted by assigning a geological meaning to homogenisation temperatures for aqueous inclusions in calcite that since trapping have suffered irreversible changes, such as volume changes in the inclusion chamber, and/or compositional change in the fluid. Stretching refers to deformation of an inclusion without any change in fluid composition leading to a density decrease.…”
Section: Introductionmentioning
confidence: 95%
“…This hydrothermal event postdates stratiform copper mineralisation and is linked to compressional deformation and metamorphism during the Lufilian orogeny. They estimated the maximum homogenisation pressure at 1.2 kbar, which is the typical pressure for decrepitation of 12-13 lm size fluid inclusions in quartz (Leroy, 1979). • Epigenetic iron-oxide-Cu-Au type mineralisation at the Kansanshi Copper Mine (Solwezi area, north-western Zambia) was studied by Speiser et al (1995) and Speiser (1994).…”
Section: Previous Fluid Inclusion Studies: Zambia and The Drcmentioning
confidence: 99%
“…Partial decrepitation results in an uncontrolled total volume increase, which must lead to¯uid density decrease if the total amount of¯uid is not lost from the system. Experimental studies by Leroy (1979) and Bodnar et al (1989) give a rough relation between inclusion size and decrepitation behaviour at 1 atmosphere con®ning pressure. Swanenberg (1980) observed this size eect in natural monophase carbonic inclusions in rocks from Faurefjell metasediments in high-grade metamorphic Precambrians of south-west Norway.…”
Section: Re-equilibration Processesmentioning
confidence: 99%